the biennial exhibition format from Art to Studio. : Analysis of the relationships and behaviors of the global network of Art Biennials previous to the Covid-19 Pandemic. (2007-2019) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2021)
This article presents the analysis carried out on the relationship networks of the participants of a series of art biennials selected in the last ten years prior to the Covid-19 epidemic.
Keywords: Art biennials; visual complexity; global contemporaneity; cultural analytics; Covid-19